The effect of inspections, rotations and client preferences on staffing decisions. (21st November 2017) - Moroney, Robyn; Knechel, W. Robert; Dowling, Carlin
Abstract: With increased regulatory focus on audits and concerns about whether audit regulation is achieving its stated aims, it is timely to investigate how regulator inspection of audit files and partner rotations may be affecting staffing decisions. This is an important issue, which affects all audits, as the calibre of staff allocated across engagements impacts the quality of audit work delivered. This study reports the results of an experiment where auditor participants allocate staff across two audits, where regulation anticipated (none, inspection, rotation) and a client request for the best staff (absent, present) are manipulated between‐subjects. We find that auditors allocate lower calibre staff when neither an inspection nor rotation is anticipated than when either is anticipated. When an inspection is anticipated, auditors allocate staff with more knowledge and compliance skills. When a rotation is anticipated, auditors allocate staff with more people skills. A client request for the best staff only has an effect when a partner is due to be rotated, where auditors allocate staff with more people skills in response to the client request. Our findings provide greater understanding of staffing decisions, which may affect audit quality if concerns around audit inspections and partner rotations are perceived by auditors as more important than the underlying risk or complexity of an engagement when allocating staff.